EKSISTENSI SENI KERAJINAN DI MUSEUM BALAPUTRA DEWA NEGERI SUMATERA SELATAN - Husni Mubarat (Besaung : Jurnal Seni Desain dan Budaya, 2017)
The art of craft in Balaputra Dewa Museum of South Sumatra is basically a reflection of the cultural values of past societies, where it contains historical, social and aesthetic values. Each of the handicraft products in the museum of Bala Putra Dewa has its own uniqueness, both in terms of engineering workmanship, materials used, and its function in the life of the community supporters. The objectives of the research are: (1) to know and understand the form and function of art of work that exist in Balaputra Dewa Museum, (2) as a medium for study and appreciation in the context of art of craft (art of craft) and culture, (3) insight and art course subject matter and design, (4) as an effort to be developed to the stage of further research. The method used is observation made through direct observation of art craft products that exist in the museum Balaputradewa Palembang. The observations made on art craft products are the types of crafts, shapes, functions and materials used. Outline of the results of this study is the function of craft art products, engineering workmanship, materials used, concepts and values contained therein.Keywords: Art Craft, Presence, Museum Balaputra Dewa Negeri Sumatera Selatan